Controlling Quality Standards to Enhance Educational Quality Assurance - Issa-Salwe, Abdisalam M; Mohamed, Abdi Ahmed; Maah, Said Ahmed Ali (Advances in Social Sciences Research Journal, 2023)
Most Somali educational institutions need to set up more structured and clearly defined curriculum plans due to the need for a body to control quality education or create standards that help regulate educational settings. Furthermore, educators need to be aware of the importance of curriculum in their institutions. They should have clearly defined objectives or goals for what educational institutions want to achieve in educating society. A curriculum serves as a roadmap for an institution's educational objectives. It reviews how a learning organisation establishes such objectives and guides how teachers plan instructions and assess learners. It refers to the strategies and tools educational institutions use to lay out a course for students to fulfil a curriculum's goals. It is also intended to help institution administrators manage teachers and hold them accountable for their actions. An institution which can help with educational quality assurance is the Education Commission (EC). EC is the appropriate organisation tasked with developing uniform educational programs. An EC can also act as a body that oversees the national educational institutions. The importance of curriculum creation will be highlighted in this paper with examples of situations when EC has authority and has established rules that educational institutions must follow. Finally, the paper will try to address the following questions: How can EC establish criteria and requirements for educational institutions to develop high-quality curricula? How can EC monitor and evaluate the performance of all level educational institutions? How can EC advise institutions on how to design curricula that strike a balance between teaching and learning?